Tumor suppressive MicroRNAs miR-34a/c control cancer cell expression of ULBP2, a stress-induced ligand of the natural killer cell receptor NKG2D - Heinemann, Anja; Diederichs, Sven (Cancer research, 2012)
Malignant cells express ligands for the natural killer cell immunoreceptor NKG2D, which sensitizes to early recognition and elimination by cytotoxic lymphocytes and provides an innate barrier against tumor development. However, the mechanisms that control NKG2D ligand (NKG2DL) expression in tumor cells remain unknown. We recently identified the NKG2DL ULBP2 as strong prognostic marker in human malignant melanoma. Here, we provide evidence that the tumor-suppressive microRNAs (miRNA) miR-34a and miR-34c control ULBP2 expression. Reporter gene analyses revealed that both miRNAs directly targeted the 3′-untranslated region of ULBP2 mRNA and that levels of miR-34a inversely correlated with expression of ULBP2 surface molecules. Accordingly, treatment of cancer cells with miRNA inhibitors led to upregulation of ULBP2, whereas miR-34 mimics led to downregulation of ULBP2, diminishing tumor cell recognition by NK cells. Treatment with the small molecule inhibitor Nutlin-3a also decreased ULBP2 levels in a p53-dependent manner, which was due to a p53-mediated increase in cellular miR-34 levels. Taken together, our study shows that tumor-suppressive miR-34a and miR-34c act as ULBP2 repressors. These findings also implicate p53 in ULBP2 regulation, emphasizing the role of the specific NKG2DL in tumor immune surveillance.